An Experiment On Social Mislearning - Erik Eyster; Matthew Rabin; Georg Weizsäcker (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
We investigate experimentally whether social learners appreciate the redundancy of information conveyed by their observed predecessorsáctions. Each participant observes a private signal and enters an estimate of the sum of all earlier-moving participantsśignals plus her own. In a first treatment, participants move single-file and observe all predecessorséntries; Bayesian Nash Equilibrium (BNE) predicts that each participant simply add her signal to her immediate predecessorś entry. Although 75% of participants do so, redundancy neglect by the other 25% generates excess imitation and mild inefficiencies. In a second treatment, participants move four per period; BNE predicts that most players anti-imitate some observed entries. Such anti-imitation occurs in 35% of the most transparent cases, and 16% overall. The remaining redundancy neglect creates dramatic excess imitation and inefficiencies: late-period entries are far too extreme, and on average participants would earn substantially more by ignoring their predecessors altogether.
Keywords: B49; 330; social learning; redundancy neglect; experiments; higher-order beliefs